2010
DOI: 10.3201/eid1607.091085
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of East African Relapsing FeverBorreliaspp.

Abstract: B. recurrentis may have evolved directly from B. duttonii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 14 publications
1
52
1
1
Order By: Relevance
“…[9][10][11][12][13][14][15] Rickettsia felis and Borrelia duttonii were also found in eastern Africa. [16][17][18] Some of them had already been described in Gabon. For example, R. felis and Bartonella quintana had been detected in some well-known vector arthropods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15] Rickettsia felis and Borrelia duttonii were also found in eastern Africa. [16][17][18] Some of them had already been described in Gabon. For example, R. felis and Bartonella quintana had been detected in some well-known vector arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies performed in sub-Saharan Africa on febrile patients, the lack of control groups composed of afebrile people represents a major pitfall that compromises a good understanding of causes of fever in areas where asymptomatic carriage of microorganisms are described. 13,17,18,24 Herein, our aim was to use molecular assays to evaluate the prevalence of bacteria, including emerging and common bacteria, as well as the prevalence of Plasmodium spp. in both febrile and afebrile children in Franceville, Gabon, where it has been recently reported that malaria prevalence had decreased from 68.9% to 17.9% among febrile patients.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few genetic loci, such as the single-copy chromosomal 16S rRNA and flabB genes 39 and the 16S-23S ribosomal RNA intergenic spacer (IGS), have been used to discriminate between the various African relapsing fever borreliae. 40 Genetic comparisons 18,19 indicate that the 16S rRNA gene exhibits two to six nucleotide differences among the four cultured species; these differences are scattered along the whole 16S rRNA gene sequence for each species, resulting in a high overall sequence similarity of 99.7-99.9% between the four species. 41 Moreover, interrogation of GenBank database indicates that these signatures are not consistent over the 37 B. crocidurae 16S rRNA gene sequences recorded in GenBank, resulting in a 1% 16S rRNA gene sequence intraspecies variation.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The IGS showed an interspecies sequence variability of 92-99%, making it a potential target to identify borreliae from vectors and from blood. 40 The IGS sequence-based phylogenetic tree clustered B. crocidurae and B. hispanica into one clade and also generated a clade comprising B. duttonii and B. recurrentis. Indeed, IGS sequencing in Tanzania mixed four B. duttonii types with two B. recurrentis types.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation